Developing supplementary English reading module for tenth-grader of senior high school SahabatQu Yogyakarta - Rudian Rudian; Imam Ghozali (Journal of English Language and Pedagogy, 2021)
The objectives of this study are to (1) develop supplementary reading materials using Contextual Teaching and Learning Approach for students of SMA SahabatQu and (2) describe the efficacy of the supplementary reading materials. This research belongs to Educational Research and Development (R&D) using a simplified six steps of (Gall, Gall, & Borg, 2003) model. In general, the result of the research shows that the developed English reading module is beneficial, useful and appropriate to be used in improving reading skills of  X graders of  Senior High School Sahabatqu. After the module was tested, the efficacy of the developed product helped the students to achieve students’ need, optimize learning independently, learning by team, broaden knowledge and improve reading skills. Furthermore, the contextual English reading module provides additional learning resources for students. The necessities of the teaching and learning English is to improve students' English skills so that they gain good in reading and understanding text and they can learn independently. They can understand WH-questions that is important in learning reading.  The efficacy of this product helps students to improve their reading skill especially to understand the topic, the generic structure, the main idea, the grammar and the vocabulary used in the text.